Konsep Tuhan dalam Pandangan Kahlil Gibran - Mohammad Shehabudin Al Hamdani; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss the concept of God in the view of Kahlil Gibran. The method used in this research is qualitative which produces descriptive data and the data collection of this research uses the method of library research (library research). The results and discussion of this research is that it is clear that Kahlil Gibran through his literary works is not only a writer, but also a philosopher with a deep soul expression. God in his view is God who exists and resides within us at a transcendental level. Khalil Gibran believes that to find God, humans must also see God's creation. The conclusion of this study is that God develops on earth and in humans. And to understand that he is the center of gravity and understand love as a means to arrive at the presence of God. In man only when he has perfected his human nature by establishing a subject-object relationship.